The influence of occupational environment on formation of psycho-emotional stress among remote pilots of unmanned aircraft systems - A. V. Shvets; V. V. Kalnysh; O. V. Maltsev (Zaporožskij Medicinskij Žurnal)
The aim of this study was to identify informative indicators and establish the level of perception of their impact on the formation of excessive psycho-emotional stress among remote pilots of unmanned aircraft systems (UASs) (class 1 “Light”) during their occupational activities.